Nota redakcyjna - Lipiński, Filip; Łuczak, Dorota (Artium Quaestiones, 2024)
The problem of borders/boundaries in art history, both ancient and modern, recurs in various guises and meanings. A border as a dividing line, structuring political, national or regional geography, is often an object of conflict that translates into both artistic practices and discourses that attempt to systematize and qualify art created in a given area, thus influencing artistic geography. Art often constitutes an attempt to answer or problematize borders on the grounds of cultural, economic, racial, etc. differences. This is the subject of numerous artistic and exhibition projects dealing with, for example, the US-Mexican or Israeli-Palestinian borders (border art) but also the questions of social and cultural divisions, artistic geographies or even boundaries within the domain of art and culture. Moreover, an urgent factor which forces us to rethink the problem of borders and identity in the context of both art of the past and the present is the ongoing war in Ukraine.